Photosynthetic Adaptation Chloroplast to Landscape - Smith, William K.; Vogelmann, Thomas C.; Critchley, Christa (Springer New York, 2004)
The impact of global change on sources, sinks, and sequestration of carbon and, ultimately, on future changes in plant distribution and biodiversity patterns depends upon the capacity of plants for light capture and CO2 assimilation. This book provides a detailed analysis of photosynthetic mechanisms across the structural and spatial hierarchy from cells to leaves, crowns, canopies, stands and landscapes. The authors question whether photosynthetic adaptations are taking place primarily at the metabolic and biochemical level, or through changes in structure and form, or both. In the interest of genetic engineering applications for plant improvement, they consider the relative importance of genes controlling both metabolic and light reactions, as opposed to the development and arrangement of photosynthetic components
Keywords: Plant Sciences; Plant Biochemistry; Plant Ecology; Tree Biology; Plant Physiology; Botany; Biochemistry; Trees; Plant physiology; Pflanzenökologie; Photosynthese; Anpassung; Biosphäre; Aufsatzsammlung